The effect of knowledge, attitude, and practice model-based health education on psychological well-being and self-efficacy of patients with concurrent cerebrovascular stenosis and coronary heart disease: a quasi-experimental study - Qiyu Zhou; Yuli Qian; Dan Zhang; Huan Xu; Bei Yuan; Wenfeng Tian; Qiong Li (Frontiers in Public Health)
ObjectiveThis research aimed to evaluate the effect of knowledge, attitude, and practice model-based health education on patients with cerebrovascular stenosis and coronary heart disease who underwent simultaneous interventional therapy.MethodsSixty patients with cerebrovascular stenosis complicated with coronary heart disease and treated in The Third People’s Hospital of Hubei Province, from February 2019 to April 2021 participated in the study. Patients were randomly assigned to either a control group (n = 30) or an intervention group (n = 30). The control group received routine nursing care, while the intervention group received knowledge, attitude, and practice-based health education. Comparisons were made between the two groups regarding satisfaction rates, anxiety, depression, knowledge, attitude, practice scores.ResultsThe intervention group exhibited a higher satisfaction level than the control group. Additionally, the intervention group showed improved self-efficacy and reduced anxiety and depression scores at discharge, 1 month, and 3 months after discharge. The intervention group achieved higher knowledge, attitude, and practice scores at all three time points compared to the control group (p < 0.05).ConclusionThe results suggest that the application of Knowledge, Attitude, and Practice Model in patients with cerebrovascular stenosis and coronary heart disease can effectively enhance psychological well-being, improve self-efficacy, and enhance understanding of the disease.